2015
DOI: 10.1121/1.4928608
|View full text |Cite
|
Sign up to set email alerts
|

Tissue physical property of the harbor porpoise Phocoena phocoena for investigation of the sound emission process

Abstract: 15The process by which sound is propagated in the head of a toothed whale is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…At the ES frontal tip ( x = 31.79mm), the melon acoustic impedance was 1.454×10 6 Pa s/m ( Fig 3 ), closely matching that of seawater, 1.54×10 6 Pa s/m [ 19 ]). This result supports the theory that the melon functions to match the acoustic impedance of seawater for the effective emission of clicks [ 13 14 , 20 ]. The distribution of acoustic impedance was more similar to Young’s modulus than it was to density.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…At the ES frontal tip ( x = 31.79mm), the melon acoustic impedance was 1.454×10 6 Pa s/m ( Fig 3 ), closely matching that of seawater, 1.54×10 6 Pa s/m [ 19 ]). This result supports the theory that the melon functions to match the acoustic impedance of seawater for the effective emission of clicks [ 13 14 , 20 ]. The distribution of acoustic impedance was more similar to Young’s modulus than it was to density.…”
Section: Discussionsupporting
confidence: 88%
“…It should be caused by the extremely large difference between the density and Young’s modulus (for example, in DCT, the rate of change of Young’s modulus fluctuated from 400–8000N/m 2 , whereas that of density ranged 0.8–1.2 g/cm 3 ). Conventional study [ 13 ] suggested that focusing distribution of Young's modulus is more important than that of density because when the acoustic impedance changes, the change rate of Young’s modulus would occupy a larger percentage than that of the density. In this study, we supported this idea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations